2015
DOI: 10.1007/s10209-015-0444-x
|View full text |Cite
|
Sign up to set email alerts
|

Location of navigation menus in websites: an experimental study with Arabic users

Abstract: While Arabic users represent by far the fastest growing language population on the Internet, research about how the peculiarities of Arabic language may shape users' web interactions is still scarce. The preferences of Arabic users for menu location in websites have been studied. Two competing arguments have been proposed regarding the best location of menus in websites: conventional design (navigation menu should be placed on that side where users expect it based on previous experience) and reading direction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…For example, 16% of subscribers of the English digital edition of the New York Times are from outside the United States (Peiser, 2019). Accordingly, during the last decade, there has been an increased interest in understanding how bilingual people process information and communicate in online scenarios as a function of the language used (their first, L1, or second language, L2) (Salmerón, Abu Mallouh, & Kammerer, 2017;Tan, Swee, Lim, Detenber, & Alsagoff, 2008;Tse, Yuen, Loh, Lam, & Ng, 2010;Walther, Neubaum, Rösner, Winter, & Krämer, 2018;Yakut & Aydın, 2017).…”
Section: Incivility In Online News and Twitter: Effects On Attitudes Toward Scientific Topics When Reading In A Second Languagementioning
confidence: 99%
“…For example, 16% of subscribers of the English digital edition of the New York Times are from outside the United States (Peiser, 2019). Accordingly, during the last decade, there has been an increased interest in understanding how bilingual people process information and communicate in online scenarios as a function of the language used (their first, L1, or second language, L2) (Salmerón, Abu Mallouh, & Kammerer, 2017;Tan, Swee, Lim, Detenber, & Alsagoff, 2008;Tse, Yuen, Loh, Lam, & Ng, 2010;Walther, Neubaum, Rösner, Winter, & Krämer, 2018;Yakut & Aydın, 2017).…”
Section: Incivility In Online News and Twitter: Effects On Attitudes Toward Scientific Topics When Reading In A Second Languagementioning
confidence: 99%
“…Most empirical studies related to UI element directionality in BiDi interfaces did not include BiDi users. A notable exception is a study with twenty-five Arabic speaker participants, that has demonstrated a preference for right-hand menus in Arabic websites [55].…”
Section: Introductionmentioning
confidence: 99%
“…The rise of islamophobia is another concern for Arabs concerned about travelling abroad. § Arab context uniqueness: There is a growing body of the research that attempts to address the culture peculiarities in Saudi Arabia [1,11], and study the Arabic users' preferences using Hofstede dimensions [8,10,13]. The participants in the ArabHCI DIS 2017 workshop raised the issues of addressing user groups culturally marginalised in the Arab region such as users with disabilities or LGBT [12,15].…”
Section: Introductionmentioning
confidence: 99%